Equity culture and the distribution of wealth - Yannis Bilias; Dimitris Georgarakos; Michael Haliassos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
Wider participation in stockholding is often presumed to reduce wealth inequality. We measure and decompose changes in US wealth inequality between 1989 and 2001, a period of considerable spread of equity culture. Inequality in equity wealth is found to be important for net wealth inequality, despite equity's limited share. Our findings show that reduced wealth inequality is not a necessary outcome of the spread of equity culture. We estimate contributions of stockholder characteristics to levels and inequality in equity holdings, and we distinguish changes in configuration of the stockholder pool from changes in the influence of given characteristics. Our estimates imply that both the 1989 and the 2001 stockholder pools would have produced higher equity holdings in 1998 than were actually observed for 1998 stockholders. This arises from differences both in optimal holdings and in financial attitudes and practices, suggesting a dilution effect of the boom followed by a cleansing effect of the downturn. Cumulative gains and losses in stockholding are shown to be significantly influenced by length of household investment horizon and portfolio breadth but, controlling for those, use of professional advice is either insignificant or counterproductive.
urn:nbn:de:hebis:30-15195
Keywords: E21; G11; 330; Wealth distribution; inequality; stockholding; equity culture